Synthesis and Characterization of Some Heterocyclic Compounds from Chalcone Derivatives and Studying of their Biological Activity - Lina Saadi (Journal of Global Pharma Technology, 2017)
In this work a preliminary step was preparation of 1-(3-((1H-imidazol-2-yl)diazenyl)phenyl)ethan-1-one (1) via coupling of diazonium salt of m-amino acetophenone with imidazole in alkaline alcoholic media which is followed to condensation with different aromatic aldehydes (p-tolualdehyde ,4-dimethyl amino benzaldehyde ) by aldol condensation in the presence of base in ethanol to give chalcones derivatives (2,3), that consider as excellent starting material for synthesis of many heterocyclic derivatives through its reaction with (hydrazine ,phenyl hydrazine ,2,4 dinitrophenyl hydrazine) to get pyrazol derivatives (4-9), likewise (2,3) react with hydroxylamine hydrochloride to get isoxazole (10,11), also (2,3) react with (urea, tiourea) to get oxazine and thiazine derivatives (12-15) , as well (2,3) react with (ethyl cyanoacetate, malononitrile) to get pyridine derivatives (16-19) ,too (2,3) react with guanidine hydrochloride to get pyrimidine derivatives (20,21). All these compounds characterized by means of FT- IR, 1H-NMR, and 13C-NMR, and follow reaction by Rf- TLC and measurements melting points. After that we studied the biological activity for all prepared compounds to ward two types of bacteria.Keywords: Azo, Chalcone, Pyrazole, Isoxzazole , Oxazine, Thiazine,  Pyridine , Pyrimidine, Biological activity.